CHARACTERISTICS OF HARDNESS AND MICROSTRUCTURE OF RECYCLED PISTONS MANUFACTURED BY SAND CASTING PROCESS - Bambang Hari Priyambodo; Handoko; Felixtianus Eko Wismo Winarto; Amida Tri Andani; Martinus Heru Palmiyanto; Kaleb Priyanto (Department of Mechanical Engineering Education, 2025)
Motorcycle piston waste, made from aluminum, is often poorly managed despite its advantages in corrosion resistance and thermal conductivity. This study aims to enhance the economic value of piston waste through recycling using the sand casting method. The melting process was conducted at a temperature of 843°C, followed by casting into sand molds. The recycled product is intended for use as a ship propeller component. Tests performed included Vickers hardness testing and microstructural analysis to evaluate the mechanical properties and material characteristics. The results showed that the recycled material exhibited an average hardness of 77.2 kg/mm², consistent with standard aluminum hardness. Microstructural analysis revealed the presence of porosity which may affect mechanical strength; however, this porosity did not reduce the material's resistance to mechanical damage and provided good toughness. Based on these findings, it can be concluded that motorcycle piston waste recycled by sand casting at 843 °C has potential for use in manufacturing high-value components such as ship propellers, considering the hardness quality and microstructural characteristics of the material.